Cerium silicate-based thin-film apatites: high conductivity and solid oxide fuel cell application. (20th April 2017) - Lee, Sunghwan; Guan, Xiaofei
Abstract: Abstract : We report on the intermediate-temperature synthesis (973 K) and operation (<750 K) of Ce4.67 (SiO4 )3 O-based thin-film oxy-apatites. The apatite thin films show the high conductivity of 0.05–0.5 S/cm and excellent stability in reducing atmosphere (<10 −17 atm), which makes promising these materials as anodes for intermediate-temperature solid oxide fuel cell (SOFC) application. The proto-type SOFCs implementing single-layer apatite and apatite/Pt bilayer anodes were fabricated and the resulting performance (e.g., peak power density of 5 mW/cm 2 at 748 K) presents notable feasibility of ZCS-based oxy-apatite anodes for thin-film SOFC devices.